SOCIO-POLITICAL DEVELOPMENT OF THE ALTAI-SAYAN REGION IN 1919–1924 - Sagalakov E. A. (Scientific Journal of Pedagogy and Economics, 2019)
The aim of the study is to analyze the socio-political development of the Altai-Sayan region in 1919– 1924. We used methods of analysis, synthesis and comparison. We have studied the institutions of society and the state, the situation of indigenous peoples and social groups in the Altai-Sayan highlands, the events of the civil war and the transition to a new economic policy based on the works of historians. The idea that the activities of the Soviet government were widely supported by the local population with minimal resistance from the exploitative elite of the indigenous peoples of the Altai-Sayan was criticized. There are examples of the fact that terror against the indigenous population of Altai, Khakassia and Shoria by the representatives of the Soviet authorities, former red partisans and immigrants caused active armed resistance. It is concluded that the policy of the Soviet government in the period under review caused strong opposition both from the right-wing parties and right-wing forces of non-socialist orientation, as well as the local, especially indigenous, population of the Altai-Sayan region. The weakening of the policy of "military communism", the restoration of elements of the market economy, an attempt to solve the "national issue", allowed to stabilize the sociopolitical situation in the region.